Estudo do desempenho térmico das envoltórias de edificações residenciais multipiso em Aracaju/SE - Filgueiras, Andrea Carla Peixoto (2019)
People have always sought better quality conditions in his dwellings and, currently, this idea is associated with the search for a minimum performance and efficiency of all the elements, components and systems that are part of the buildings. Apart from providing comfort for users, the thermal performance of a building influences directly on energy efficiency and contributes in a very incisive way to the sustainability of the world. With the norms and the ideal sustainable scenario, it is essential that the constructive systems of the facades and roofs of the buildings present a minimum thermal performance. The general aim of this work is to verify if the typical constructive system adopted on the envelopes of residential multifloor buildings in the city of Aracaju/SE, meets the requirements of the minimal thermal performance of the Performance Standards. It was an exploratory research, divided in four stages, with design through qualitative and quantitative methods. The first stage was the bibliographic review, followed by the stage of structured interviews with representatives of incorporating companies and/or local builders, using open and closed questions. The third stage was a case study, with simplified method and computer simulation, using a sample of the characteristic standard of the systems used in the local envelopes. Finally, analysis of results and conclusion. The results of the interviews with the companies were significant for the work, where it was noticed that the criteria used to determine the envelope have priorities in other points, instead of the thermal performance that the buildings must provide. However, thermal performance is a growing criterion for the companies concerning the development of projects and constructions of multi-floor residential buildings, due to the implementation of the Performance Standards. For the results of the simplified method, the standard system met the minimal thermal performance of the envelope. However, in the simulation method it did not reach the desired level, according to Performance Standards. Therefore, this research shows the need for a thermal performance study in the envelopes in a warm and humid weather. It is expected that compliance with minimum thermal performance will be achieved by developing projects and specifications aimed at the best thermal quality of the multi floor residential buildings envelopes, favoring the thermal comfort of users and the overall thermal efficiency.